بلاغة التراكيب القرآنية عند الإمام عبد الحميد بن باديس من خلال تفسيره مجالس التذكير من كلام الحكيم الخبير - مرقاجي, سليم; زغداني, محمد الهادي (University of eloued جامعة الوادي, 2021)
"تناولت هذه الدراسة بلاغة التراكيب القرآنية، عند الإمام ابن باديس، من خلال تفسيره للقرآن الكريم، وحاولت رصد عنايته ببيان بلاغتها، ومدى اعتماده عليها في كشف معاني الخطاب القرآني، ولمعالجة هذا الإشكال انتهجنا الخطة الآتية: مبحث تمهيدي للتعريف بابن باديس وكتابه ̋مجالس التذكير̏، ومبحث أول: يتعلق ببلاغة الصور البيانية عند الإمام، وثان يتناول بلاغة الأساليب اﻟﻘﺮآنية عند الإمام، وأثرها ﰲ إبراز المقاصد والأغراض القرآنية. وقد خلصنا إلى جملة من النتائج أهمها: أن الإمام كانت له عناية معتبرة بالتراكيب اﻟﻘﺮآنية، كونها مهمة ومعينة على تجلية المعاني وتوجيهها وضبطها، وإقرار الأحكام الشرعية، وكذا ترسيخ القيم التربوية والأخلاقية، ودعوته إلى العناية بعلوم اللغة العربية للفهم الدقيق للنصوص الشرعية. ""This study dealt with the eloquence of the Qur’anic structures, according to Imam Ibn Badis, through his interpretation of the Holy Qur’an, and tried to monitor his care in explaining their eloquence, and the extent to which he relied on them in revealing the meanings of the Qur’anic discourse. To address this problem, we have adopted the following plan: An introductory study to introduce Ibn Badis and his book, ""Majalis al-Tadhkir"". The first topic relates to the eloquence of graphic images at the Imam, and the last topic deals with the eloquence of Qur’anic methods for the Imam, and their impact on highlighting Qur’anic purposes. We had a number of results, the most important of which are: The imam had considerable care with the Qur’anic structures, as they are important and help in clarifying meanings, directing and controlling them, approving legal rulings, as well as consolidating educational and moral values, and calling him to take care of the sciences of the Arabic language because they have a profound impact on the accurate understanding of religious texts. "
لغة ودراسات
Keywords: بلاغة / القرآنية، مجالس التذكير /الحكيم الخبير، الإمام عبد الحميد بن باديس; The eloquence of Quranic structures, reminder boards from the words of the expert wise, Imam Abdul Hamid bin Badis